Play of a fiddle : traditional music, dance, and folklore in West Virginia - Milnes, Gerald (The University Press of Kentucky, 2009)
Play of a Fiddle gives voice to people who steadfastly hold to and build on the folk traditions of their ancestors. While encountering the influences of an increasingly overwhelming popular culture, the men and women in this book follow age-old patterns of folklife and custom, making their own music and dance in celebration of them. Shedding new light on a region that maintains ties to the cultural identities of its earliest European and African inhabitants, Gerald Milnes shows how folk music in West Virginia borrowed rhythmic, melodic, and vocal forms from the Celtic, Anglo, Germanic, and Af.